PENGARUH TINGKAT PENDIDIKAN DAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (TAHUN 2008 – 2012) - Puput Evira Iskarno; Harya Kuncara W.; Dicky Irianto (Faculty of Economics, State University of Jakarta., 2014)
The purpose of this study was to determine and analyze the effect of the level of education and infrastructure to economic growth. The object of this research is the number of workers according to the highest educational level attained at the level of the SMTA as data objects of variable levels of education, length of road per area of the province as a data object of infrastructure variables, and Gross Domestic Product (GDP) as data objects of variable economic growth obtained from the Central Bureau of Statistics. The scope of this study includes data from 32 provinces in Indonesia in 2008-2012, by combining the data from the Riau Islands province of Riau Province in the data. The method used in this research is ex post facto method with multiple regression analysis approach. This study led to the conclusion that there is a significant positive effect between the level of education on economic growth. There is a significant positive impact of road infrastructure on economic growth, and at the same time, there is a significant positive effect between level of education and infrastructure to economic growth. Keywords: economic growth, level of education, GDP, infrastructure